Al-Lontarā (al-Nuṣūṣ) al-Muktamilah li-Tārīkh Wajo: Nāẓrah Jadīdah fī Awwal Dukhūl al-Islām ilá Wajo - Ilyas, Husnul Fahimah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2011)
This article discusses the reconstruction of Islam in Wajo by looking at Lontaraq Suqkuna Wajo of Datuk Sangaji Sengkang collection as the main source of the study. As a script, lontaraq is an evolutionary change of the Kawi script which has been being modified and has long been used as evidenced by the finding of inscription on the fort site of Somba Opu and Lagaligo epics written before 1600. Lontaraq script occupies an important position in the cultural history of Bugis Makassar. For Bugis, lontaraq has two meanings: (1) lontaraq as an history and science and (2) lontaraq as a writing.DOI: 10.15408/sdi.v18i3.429